Monitoring Kualitas Air pada Tambak Udang berbasis Internet of Things dengan Protokol Komunikasi ZigBee - Dwiki Ansarullah; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Aquaculture is a commodity that is quite important to meet the fulfillment of Indonesian market in addition to fishery. Water quality in a pond farming is an aspect that we need to pay attention to that for the sustainability of the biota inside. The application of pond farming in a highland cities, low air temperature, frequently become an obstacle. Besides that, 24 hours water quality check is a challenging things for pond farmers. This research is using Internet of Things with the support of communication protocol ZigBee which can make an easier way for pond farmers to access the current condition of their ponds. With expectations shrimp farmers can increase their income and didn't suffer a loss because of problems they faced. In its implementation a sensor node that contain of temperature sensor and a turbidity sensor is placed on the object of research which is home-base shrimp pond farming. Then the obtained data is sent to the node gateway and then the data will be forwarded to ThingSpeak webserver. From the testing that has been done using communication protocol ZigBee, the data transmission is quite good. In a tests that held indoors, an average delay is 1.8 s, packet loss to 0%, and the average throughput is 211.023 kbps.